Vitamin D May not be Crucial: Association between Serum Vitamin D Level and Pregnancy-Induced Hypertension-A Meta-Analysis - Changxing Cui; Xiaoyan Huang; Yuanqing Cui; Shaochang Jiang; Xiaoyan Yao; Xuelong Li (Clinical and Experimental Obstetrics & Gynecology)
Background: The association between vitamin D and pregnancy-induced hypertension (PIH) remains contentious. The aim of our study was to evaluate the existence of an association between serum vitamin D levels and the incidence of PIH. Methods: We conducted a literature search in PubMed, the Cochrane Library, and Embase databases in June 2024 using the following search terms: 25-hydroxyvitamin D (25(OH)D), Vitamin D, 1,25(OH)2D, VD, 1,25-dihydroxyvitamin D or 25(OH)D, combined with PIH. Two reviewers independently screened the literature based on inclusion and exclusion criteria. Data were then extracted and assessed for quality. Comparisons were made between the highest and lowest categories of serum vitamin D levels. Relative risks (RRs) and 95% confidence intervals (CIs), adjusted for multivariable effects, were pooled using a random-effects model. A two-stage dose-response meta-analysis was used to evaluate the trends. Results: 17 studies met the inclusion criteria. Of these, 11 prospective studies investigated the relationship between vitamin D levels and gestational hypertension, involving 8834 events and 17,104 participants. The results showed that vitamin D was only marginally associated with hypertensive disorders in pregnancy (summary RR = 0.99; 95% CI: 0.97–1.02; I2 = 67.5%; p = 0.001). However, 6 case-control studies investigated the relationship between vitamin D levels and gestational hypertension, involving 80,814 events and 330,254 participants. The results showed that vitamin D is not associated with pregnancy hypertensive disorders (summary RR = 1.09; 95% CI: 0.84–1.41; I2 = 75.4%; p = 0.001). In the subgroup analysis, the pooled effect of 25-hydroxyvitamin D (25(OH)D) showed a slight association with gestational hypertension (pooled RR = 0.99; 95% CI: 0.96–1.02; I2 = 72.6%; p = 0.000). The dose-response analysis showed that increasing vitamin D doses are marginally associated with a decrease in the incidence rate. Conclusions: Our research suggests that the risk of PIH may not be related to the vitamin D levels. Our research supports the hypothesis that gestational hypertension may not be associated with low levels of vitamin D, indicating that the role of vitamin D may not be significant.